Integration of Scheduling & Control for Sequential Batch Processes: An Iterative Approach. Issue 1 (2018) - Misra, Shamik; Gudi, Ravindra D.
Abstract: The need for integration of scheduling and control layers of an enterprise decision making framework is getting more relevant in recent times due to agile market conditions and increasing competition. To exercise automation in its entirety, information flow between various decisions making levels are necessary and integration of these levels not only ensures information exchange but also helps to reach an improved optimal solution for the whole system. In this paper, an iterative framework is outlined which is effective in facilitating integration and information exchange between the control and scheduling layer with reasonable computational efficiency. The framework is applied on a multi-unit, multi-task batch process case study taken from Chu & You (2014). The result demonstrates that the proposed iterative framework is computationally efficient and facilitates integration between the layers in an improved manner, which in turn shows better performance than the sequential approach.